Untangling neural networks with dual retrograde transsynaptic viral infection - Ohara, Shinya; Inoue, Ken-ichi; Witter, Menno P.; Iijima, Toshio (Frontiers in Neuroscience, 2009)
Using recombinant rabies virus (RV), we developed a dual transsynaptic retrograde tracing technique in the rat central nervous system. Two strains of recombinant RV, injected into two separate loci of the brain, were taken up through axon terminals and carried retrogradely and transsynaptically from neuron to neuron. Each viral strain expresses a unique marker in infected neurons. Therefore, neurons that project transsynaptically to two brain loci can be detected by double-labeling. In this review, we will introduce the advantage of dual viral tracing by recombinant RV, and will also address some potential weaknesses of this technique. Although false negative results may arise due to interference between two strains of RV, the ability of the recombinant RV to visualize the morphology of the infected cell and to infect primates in addition to rodents will make this technique a potential tool to provide new insights into the complex organization of brain networks.